1996
DOI: 10.1089/jir.1996.16.381
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Tumor Necrosis Factor Secretion by Cord Blood Mononuclear Cells UponIn VitroStimulation withListeria monocytogenes

Abstract: We examined the production of tumor necrosis factor (TNF) by mononuclear cells (MNC) after incubating adult or cord blood MNC with Listeria monocytogenes in vitro. With adult MNC cultures, we found that TNF activity reached a peak at 6 h (606 +/- 120 x 10(3) units/liter) and declined to the baseline by day 3. In contrast, using cord blood MNC, we found that TNF activity increased gradually reaching a peak at 24 h. In addition, the peak TNF activity using newborn MNC (189 +/- 26 x 10(3) U/liter) at 24 h was sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…This approach resembles published assays for cytokine production by cord blood monocytes (LM precursors). However, contrary to cord blood studies that found TNF-␣ to be developmentally regulated (11,12,21,22), our data show that LM activation induced a nearly identical magnitude of TNF-␣ in the preterm versus term groups (Fig. 4A).…”
Section: Discussioncontrasting
confidence: 99%
“…This approach resembles published assays for cytokine production by cord blood monocytes (LM precursors). However, contrary to cord blood studies that found TNF-␣ to be developmentally regulated (11,12,21,22), our data show that LM activation induced a nearly identical magnitude of TNF-␣ in the preterm versus term groups (Fig. 4A).…”
Section: Discussioncontrasting
confidence: 99%
“…Cord blood monocytes show impaired chemotaxis and capacity to synthesize TNF-a but normal phagocytosis compared with that seen in adult monocytes. 41,42 DCs in the normal placenta preferentially induce T H 2 differentiation by naive T cells, 43 although it is not clear whether the influence of placental DCs persists into postnatal life. At birth, there is a modest reduction in circulating DC numbers relative to that seen in adults, 44 with many neonatal DCs appearing relatively immature, with lower levels of intercellular adhesion molecule 1, class I MHC, and II MHC expression.…”
Section: Attenuation Of Innate Immunity and Apc Function In Childhoodmentioning
confidence: 99%
“…Term cord-blood monocytes have decreased production of a number of cytokines, including TNF-a (20), in comparison to the adult. Although cord-blood mononuclear cells can phagocytose at a level comparable to the adult, chemotaxis is reduced (21).…”
Section: Macrophages and Dendritic Cellsmentioning
confidence: 99%